2007
DOI: 10.1007/bf03175089
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cytotoxic activities of extracts from (Tunisian)Rhamnus alaternus (Rhamnaceae)

Abstract: The petroleum ether, chloroformic, ethyl acetate, methanolic, Total Oligomers Flavonoids (TOF) enriched extracts, water extract as well as its fractions A 1 , A 2 , A 3 obtained from aerial parts of Rhamnus alaternus, a Tunisian-Mediterranean medicinal species, were investigated for the contents of phenolic compounds, cytotoxic activity against the K562 human chronic myelogenous leukaemia cell line and L1210 leukaemia murine cells and for antibacterial activity against Gram positive and Gram negative bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Likewise it appears from the IC 50 values of superoxide anions measured in the presence of TOF and methanolic extracts (respectively 138 and 183 lg/ml) that TOF extract is the most potent superoxide scavenger (Ben Ammar et al, 2007a), as it was enriched in polyphenolic compounds compared with the methanolic extract (Ben Ammar et al, 2007b). The antioxidant and free radical-scavenging potential of the flavonoids (1-3) tested in this study could justify and explain the same activities obtained with the original extracts, as these flavonoids are the major components of the TOF and the methanolic extracts.…”
Section: Anti-lipid Peroxidation Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise it appears from the IC 50 values of superoxide anions measured in the presence of TOF and methanolic extracts (respectively 138 and 183 lg/ml) that TOF extract is the most potent superoxide scavenger (Ben Ammar et al, 2007a), as it was enriched in polyphenolic compounds compared with the methanolic extract (Ben Ammar et al, 2007b). The antioxidant and free radical-scavenging potential of the flavonoids (1-3) tested in this study could justify and explain the same activities obtained with the original extracts, as these flavonoids are the major components of the TOF and the methanolic extracts.…”
Section: Anti-lipid Peroxidation Effectmentioning
confidence: 96%
“…We have also reported others biological activities of R. alaternus extracts: antibacterial and antiproliferative. In human cells, extracts of R. alaternus leaves modulate the expression levels of genes implicated in both DNA repair and oxidative defence systems (Ben Ammar et al, 2007a, 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, esculin did not show any mutagenicity in the strains S. typhimurium TA104 and S. typhimurium TA102. The absence of mutagenicity in the presence of rutin, oligorutin fractions, esculin and oligoesculin fractions, in the two S. typhimurium strains TA102 and TA104, with and without (S9) activation system at any tested dose of the different fractions, indicated that DNA did not seem to be a relevant target for these molecules (Ben Ammar et al, 2007).…”
Section: Fractionsmentioning
confidence: 98%
“…Rhamnus alaternus leaves contain many active compounds,[ 3 4 5 ] and experimental studies have demonstrated that extracts of R. alaternus leaves possess different biological activities. [ 6 7 8 9 10 11 12 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%